Factors Affecting the Clothing Purchase Intention of Young Consumers through Online (Journal of Population and Development, 2024)
This research paper was conducted for the purpose of identifying the factors that influence the clothing purchase intention of young consumers who are used to shopping through online market. To serve the purpose of the study, a total of 100 (one hundred) respondents were selected through convenience sampling. The collected data were analyzed using Pearson correlation and multiple regression analysis. The authors found that all factors namely time & convenient, perceived past experience, perceived security; product variety, Website design and Service quality have significant impact on online clothing purchase intention of young generation. Through this study the authors suggest that social media has a beneficial effect on how customers behave while buying clothing companies. Social media experiences online are influencing study participants' decisions to purchase intention of clothing from a certain brand. The authors expect that this study will help the clothing brands to understand the purchase intention of their young consumers through online and it will help them to take necessary step to increase their online sales based on the significance level of each factor and contribute to the clothing industry.